EVALUASI KONDISI KERUSAKAN BANGUNAN PENGENDALI LAHAR DI SUNGAI KRASAK - Cahyo Dita Saputro (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
The sabo dam located in the Krasak river area, which loads Mount Merapi eruptions, has been built more than 20 years old. This circumstance certainly affects the physical condition and function of the 23 sabos. Therefore, it is valuable to do a research which focuses on the damage sabo building to find out the necessary maintenance to take, so that the sabo building can be functioned properly. The method of the data collection is direct observation to the location. The results of the study indicate that 22 buildings are still in good category and 1 building is in a moderately damaged condition.